Faculty success in the academy : tips, tools, and resources for success - Tomlin, Antione D.; Smith, Hiawatha (Research, theory, and practice within academic affairs., 2025)
Higher education continues to evolve and transform, with faculty being an essential component of this establishment.Mentoring is vital to the success of faculty, which can result in positive benefits in the development and eventual success of new faculty members. This mentoring traditionally assists them in acclimatizing to the university and academic environments. However, the ultimate goal should be to assist early career faculty with reaching success beyond their graduate school preparation. Thus, the foundation of effective mentoring should include a network of support, which should include advising, guides, and resources for faculty success, but these components are not always present. Faculty Success in the Academy: Tips, Tools, and Resources for Success fills a need within higher education faculty development, mentoring, and support. It accomplishes this by serving as a guide for new faculty, a rejuvenator for existing faculty needing a boost, and an opportunity for all faculty to identify opportunities that will help them to assimilate as valued members of the academy. Higher education is often a space for transition, conflict, and unanswered questions without a safe space to explore these concerns. This book highlights various faculty voices across the spectrum of higher education who openly share their knowledge to support other colleagues within this unique space. Readers can use this book as a window, mirror, or sliding glass door to help jumpstart or restart their success in the journey of higher education. Faculty Success in the Academy helps readers enhance their knowledge, skills, and dispositions to further their career in higher education. Each chapter extends knowledge beyond what might be present within the readers' own university, bringing to light resources and opportunities that might not otherwise be openly shared but can be beneficial to the success of all faculty.